Electromagnetic Fields and Waves in Fractional Dimensional Space - Zubair, Muhammad; Mughal, Muhammad Junaid; Naqvi, Qaisar Abbas (SpringerBriefs in Applied Sciences and Technology,, 2012)
This book presents the concept of fractional dimensional space applied to the use of electromagnetic fields and waves.  It demonstrates the advantages in studying  the behavior of electromagnetic fields and waves in fractal media. The book presents novel fractional space generalization of the differential electromagnetic equations as well as a new form of vector differential operators in fractional space. Using these modified vector differential operators, the classical Maxwell's electromagnetic equations are worked out. The Laplace's, Poisson's and Helmholtz's equations in fractional space are derived by using modified vector differential operators.